Plan estratégico de comunicación interna para Perú Inter Cargo (PIC) - Larco Valderrama, Victor Alberto (2021)
Perú Inter Cargo (PIC) is a company with 40 years in the peruvian market and is considered one of the three most important logistics operators in the country. It has eight different lines of business and is recognized by its clients for its efficiency and commitment. However, internally, the scenario is different. Leaders do not feel committed to the corporate culture and, consequently, this feeling is transferred to their teams. For this reason, the objective of this work is to present a strategic internal communication plan with neuralgic adjustments to improve the perception of leaders and collaborators towards the company, considering empathy among colleagues, the current COVID-19 situation and the coherence between messages and daily facts. In this way, communication will be a meaningful story for both emitters and receivers of messages this way, communication will be a meaningful story for both the senders of the messages and the receivers; that is, both those who send the messages and those who receive them will be able to contrast the same statements with the facts and the environment, thus determining that they are in line with reality and concluding that there is coherence, avoiding a dichotomy in communication. All this in order to encourage their commitment to the corporate culture, increase the sense of belonging and reduce the high turnover rate.